Assembly of polyethyleneimine in the hexagonal mesophase of nonionic surfactant: effect of pH and temperature - Sharma, Kamendra P.; Choudhury, Chandan Kumar; Srivastava, Sonal; Davis, Hilda C.; Rajamohanan, P. R.; Roy, Sudip; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2011)
We investigate the dispersion of a pH responsive polymer, polyethyleneimine, PEI, in a hexagonal (H(1)) mesophase of a nonionic surfactant, C(12)E(9), and water, at pH ranging from basic (pH = 12.8) to acidic (pH = 1). While the C(12)E(9)/H(2)O phase behavior is independent of pH, we demonstrate that, in the PEI/C(12)E(9)/H(2)O system, changing the pH influences PEI-C(12)E(9) interactions, and thus, influences the isotropic-H(1) phase transition. With decrease in pH, there is increasing protonation of the PEI chain, and consequently, the chain extends. We show, using a combination of SAXs, optical microscopy and visual experiments, that the inclusion of PEI in a 1:1 surfactant water mixture, lowers the hexagonal-isotropic transition temperature, T. At higher pH = 12.8 T(HI) shows a pronounced decrease from SO to 13 degrees C on addition of PEI, and the PEI/C(12)E(9)/H(2)O system forms a transparent gel. At pH = 1, we observe qualitatively different behavior and an opaque gel forms below T(HI)= 25 degrees C. The isotropic-H(1) transition, in turn, influences the phase separation of PEI chains from the C(12)E(9)/H(2)O system. 2D NMR ROESY data provides evidence that there are strong surfactant PEI interactions at high pH that significantly reduce at lower pH. The NMR data is in accord with molecular dynamics simulations that show that surfactants strongly aggregate with unprotonated PEI chains, but not with fully protonated chains; thus, in this system, the pH controls a cascade of microstructural organization: increasing pH decreases chain protonation and increases polymer-surfactant interactions, resulting in suppression of the isotropic-H(1) transition to lower temperatures, thus, influencing the phase separation of PEI from the surfactant/water system.